Utilização de técnicas de realidade virtual para treinamento de operação de termo-vácuo na manutenção de óleo transformadores de potência - TEIXEIRA, Willie Duarte (Universidade Federal do Pará, 2018)
It is a consensus among the companies that work in the National Interconnected System (SIN), that there is an essential qualification of their employees, to avoid financial losses and mainly physical damages to those involved in operational activities. In the operational context of the SIN one of the most important processes in preventive and corrective maintenance for substation equipment of the the treatment of the insulating mineral oil. Insulating mineral oil has the role of raising the insulation of the active parts of high-voltage equipment, thus maintaining the Physical-Chemical conditions within the standards, becomes essential for the proper functioning of equipment that operates in high- voltage. The present work uses Virtual Reality techniques in the creation of a virtual training environment for the operation of term vacuum, which are machines responsible for the treatment in mineral insulating oil. The proposal of this work was to bring qualitative and quantitative gains to the process of training professionals who operate or operate such equipment, with a focus on those who are in the process of training in the formal educational institutions, more specifically for the use in disciplines, such as electrical machinery and other related ones.